2020
DOI: 10.3390/rs12183027
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Water Bathymetry Based on Inherent Optical Properties Using High Spatial Resolution Multispectral Imagery

Abstract: Bathymetric surveys are of great importance for submarine topography mapping and coastal construction projects. They are also of great significance for terrain surveys of islands and coastal zones, maritime navigation and marine management planning. Traditional ship-borne water depth measurement methods are costly and time-consuming, therefore, in recent years, passive optical remote sensing technology has become an important means for shallow water depth measurements. In addition, multispectral water depth op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…While the authors invested in thorough preprocessing of the image data based on Fast Line-of-Sight Atmospheric Analysis of Spectral Hypercubes (FLAASH) and the Cloud Shadow Approach (CSA) for atmospheric corrections, they only apply a simple band ratio model as basis for their colour-to-depth regression. Zhang et al (2020) developed an Inherent Optical Parameters Linear Model (IOPLM) to estimate shallow water bathymetry of a coastal scene based on WorldView-2 and Sentinel-2A multispectral images. Cahalane et al (2019) compare different satellite datasets (Landsat 8, RapidEye, and Pleiades) and use a log ratio transform to derive bathymetry.…”
Section: Related Workmentioning
confidence: 99%
“…While the authors invested in thorough preprocessing of the image data based on Fast Line-of-Sight Atmospheric Analysis of Spectral Hypercubes (FLAASH) and the Cloud Shadow Approach (CSA) for atmospheric corrections, they only apply a simple band ratio model as basis for their colour-to-depth regression. Zhang et al (2020) developed an Inherent Optical Parameters Linear Model (IOPLM) to estimate shallow water bathymetry of a coastal scene based on WorldView-2 and Sentinel-2A multispectral images. Cahalane et al (2019) compare different satellite datasets (Landsat 8, RapidEye, and Pleiades) and use a log ratio transform to derive bathymetry.…”
Section: Related Workmentioning
confidence: 99%
“…The research areas in previous SAR shallow sea underwater topography detections have mainly been offshore shallow areas. For the remote sensing detection of the island reef topography, the main methods are analysis models, semianalytical semiempirical models and statistical models based on optical remote sensing images [22][23][24]. The detection effect of SAR for the underwater topography of islands and reefs is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [22] introduced IOPs in turbid waters to retrieve the euphotic zone depth in inland waters using a modifi ed quasi-analytical algorithm (QAA) . Zhang et al [23] propose d a linear model known as the inherent optical parameter linear model (IOPIM) to estimate shallow-water depth using high-spat ial resolution multispectral images. The findings from the IOPI M study demonstrated the potential of using inherent optical par ameters (IOPs) to enhance the accuracy of water depth estimatio n. Huang et al [24] proposed an updated quasi-analytical algorit hm (UQAA) and verified its feasibility .…”
mentioning
confidence: 99%